From structural determination of natural products in complex mixtures to single cell resolution: Perspectives on advances and challenges for mass spectrometry - Lopes, Norberto Peporine; Roberto da Silva, Ricardo (Frontiers in Natural Products, 2023)
The search for new Natural Products is one of the oldest interests for research in chemistry. The history of this discipline is very prolific, from its initial uses as medicine to advanced omics strategies to understand the mechanics of biological controls in living cells. The discoveries of morphine, penicillin, taxol and many other natural products revolutionized human health. During the last 40 years, excellent reviews published by Dr. David Newman and Dr. Gordon Crag have revealed that the pharmaceutical industry’s research into natural products has lost some of its steam. Nevertheless, new natural products for antimicrobials, antifungals, and anticancer drugs remained the main alternative. Furthermore, research institutes have seen great vigor, and several startup companies have emerged worldwide, seeking therapeutic alternatives based in natural products. Innovations on spectrometric hardware, allowing broader coverage of chemical classes and spatial mapping, and in software, enabling the interpretation of large volumes of data, afforded a renewed interest in natural products and are considered the most important enabling technology for the new companies. In this perspective article we give some historical context to exciting developments, on software and spatial resolution, that promise to pave the way for a bright future of Natural Products research.